An application of proportion compass in basic education education to study the proportionality theorem (Research, Society and Development, 2022)
Research focused on the history and teaching of mathematics, which allow dialogues based on their interfaces, are expanding in Brazil, mainly those developed through the study of historical mathematical instruments. Following the same perspective, this article presents an application of activity developed when studying the instrument, compass of proportion, contained in the treatise L'usage du compas de proportion published in 1631, by Didier Henrion. The objective is to show the application of the activity arising from handling and studying the historical instrument, the proportion compass, allowing to signify and re-signify the processes of geometric construction of the proportionality theorem. In which, the methodology is based on the qualitative approach, aided by group work in the application of the activity. Regarding the results, the autonomy of the students was highlighted for being able to investigate and try to solve the problem, in which it made it possible to remember concepts of parallelism, perpendicularism, line segments, straight lines, transversal lines, some even managed to identify that they were working with the theorem of proportionality. Therefore, it is concluded that from the use of lines of equal parts of the instrument compass of proportion it was possible to evidence didactic potential when studying theorem of proportionality through the process of development of the geometric design.